Peningkatan Keaktifan Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Numbered Heads Together (PTK pada Siswa Kelas X B MA Assalaam Temanggung Semester Genap Tahun Ajaran 2014/2015) - Setyawan, Muhammad Yusuf; , Dra. Sri Sutarni, M.Pd (2015)
The purpose of this research is to improve the students' activeness of learning mathematics by using numbered heads together technique of cooperative learning method of X B grade of MA Assalaam Temanggung. The type of the research is Classroom Action Research (CAR) which is collaboratively conducted between the mathematics teacher and the reseacher. The subject of the research is the students of X B grade of MA Assalaam which consists of 27 students and thhe teacher as the collaborator. The technique of collecting data used by the researcher are interviewing, observing, field-notes, documentations, and test method. The technique of analyzing data used by the researcher is data collection, data reduction, data display, and verification and drawing. The data validation could be measured by using source triangulation and tachnic triangulation. The result of the research is to know whether there is an improvement of the students' activeness of learning mathematics which can be seen based on the indicators as follows: (1) The students who are paying attention to the teacher during the teaching learning process in pre-cycle are 8 students (29,63%), and after cycles become 22 students (81,48%); (2) The students who ask or answer questions during the teaching learning process in pre-cycle are 5 students (18,51%), and after cycles become 19 students (70,37%); (3) The students who are expressing opinion during the teaching learning process in pre-cycle are 6 students (22,22%), and after cycles become 18 students (66,67%). It can be concluded that the use of numbered heads together technique of cooperative learning method can improve the students' activeness of learning mathematics.